2006
DOI: 10.1140/epje/i2006-10051-y
|View full text |Cite
|
Sign up to set email alerts
|

Citric-acid-coated magnetite nanoparticles for biological applications

Abstract: Water-based magnetic fluids, generally intended for biomedical applications, often have various coating molecules that make them stable and compatible with biological liquids. Magnetic fluids containing iron oxide particles have been prepared by a co-precipitation method, using citric acid as stabilizer. The magnetic particles of the magnetic fluids were obtained by chemical precipitation from ferric (FeCl(3)) and ferrous salts (FeSO(4) or FeCl(2)) in alkali medium (ammonia hydroxide). Citric acid was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(128 citation statements)
references
References 16 publications
3
122
0
3
Order By: Relevance
“…We observed that for the synthesis in which we use the solvent, the surfactant can be removed better compared to syntheses without solvent -but not totally. As we do not want risk the increase of the particle size by thermal treatment for the removal of organic residues, we tested another 'washing' method called "ligand exchange" [30][31][32]. For this ligand exchange, we start by collecting the material first by using centrifugation after the synthesis.…”
Section: Washing Procedures Of Limnpo 4 Nanoparticlesmentioning
confidence: 99%
“…We observed that for the synthesis in which we use the solvent, the surfactant can be removed better compared to syntheses without solvent -but not totally. As we do not want risk the increase of the particle size by thermal treatment for the removal of organic residues, we tested another 'washing' method called "ligand exchange" [30][31][32]. For this ligand exchange, we start by collecting the material first by using centrifugation after the synthesis.…”
Section: Washing Procedures Of Limnpo 4 Nanoparticlesmentioning
confidence: 99%
“…CA can prevent the aggregation of magnetic particles effectively owning to the steric and electrostatic repulsive barrier of the ionized layer of citrate coating on magnetite or maghemite [19][20][21][22][23][24]. In general, empirical doses, sometimes huge amounts [19,20,24] are simply added to magnetite just after precipitating nanoparticles. Our adsorption study showed that the high affinity limit is reached at ∼0.1 mmol CA on 1 g magnetite (Fig.…”
Section: Humate and Citrate Adsorption On Magnetite Nanoparticlesmentioning
confidence: 99%
“…Magnetic nanoparticles sources were consistent with magnetite stabilized with citric acid (CA) and respectively sodium oleate (SO), that were supplied as adequate volumes from various dilutions of the corresponding aqueous magnetic fluids (CA-MF and SO-MF) [15][16]. The dilutions (in distilled water), that favored the magnetite reversible complexation with the drug molecules, were: C1 = 1 ml CA-MF + 9 ml water; C2 = 2 ml CA-MF + 8 ml water; C3 = 4 ml CA-MF + 6 ml water for magnetitecitric acid complexation with rifampicin; C4 = 5.0 ml SO-MF + 5.0 ml water; C5 = 2.5 ml SO-MF + 7.5 ml water; C6 = 1.25 ml SO-MF + 8.75 ml water for magnetite-sodium oleate complexation with sodium diclofenac.…”
Section: Methodsmentioning
confidence: 99%